Edukasi Pengenalan Gejala Penyakit TBC Paru dan Pencegahannya pada Masyarakat Suku Baduy - Effendi, Ida; Devita, Arleen; Utama Sutanto, Hans; Yuliana; Bachir Nugraha Wirabrata, DA Achmad (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Pulmonary tuberculosis is one of infectious disease that remains a problem in Indonesia. In 2023, on global scale, Indonesia is a second country with the most TB cases. Baduy people is a tribe in Indonesia that has strong customs and traditions. Health report revealed that the incidence of TB morbidity and mortality in the Baduy Tribe has increased. Local wisdom in the Baduy Tribe needs to be preserved, one of which is by having a healthy Community. Community service activities (PkM) were carried out with the aim of improving the health status of the Baduy people. Counseling education was held on August 8, 2025, in the hall of SDN 02 Baduy Luar, Cisimeut Village, Leuwidamar District, Banten. The target of the activity was the Baduy Community aged >12 years. Education on Recognizing the Symptoms of Pulmonary TB and Its Prevention in the Baduy Tribe was given by presenting many informations about Tuberculosis. Assessment of the knowledge of PkM participants was obtained by providing several pre- and post-counseling questionnaires. Forty seven participants showed an increase in understanding of TB disease starting from the causes of the disease, symptoms of the disease, TBC transmission, sputum examination, the importance of early detection and regular treatment of TBC in the Baduy Tribe community. Good understanding is expected to have enefits in the form of improved health status in the Baduy community. Sustainable health education should be provide to achieve greater benefits.